2006
DOI: 10.1136/thx.2005.056119
|View full text |Cite
|
Sign up to set email alerts
|

Overnight prescription of oxygen in long term oxygen therapy: time to reconsider the guidelines?

Abstract: Background: Guidelines for long term oxygen therapy (LTOT) recommend increasing oxygen flow by 1 l/min overnight. A study was undertaken in patients with COPD on LTOT to determine the prevalence of overnight desaturation if the usual oxygen flow rate is not increased at night, whether resting oxygen saturation predicts overnight desaturation, and whether overnight desaturation correlates with health related quality of life (HRQL) and sleep quality. Methods: A cross sectional prospective study was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Several studies have suggested that a flow rate established from resting ABGs while awake may not allow adequate oxygenation overnight with patients spending only between 72% and 77% of the time with SpO 2 >90% overnight 46 49 50. Patients with more severe COPD and worse daytime ABGs spent a significantly greater proportion of the night with hypoxaemia 51.…”
Section: Long-term Oxygen Therapymentioning
confidence: 99%
“…Several studies have suggested that a flow rate established from resting ABGs while awake may not allow adequate oxygenation overnight with patients spending only between 72% and 77% of the time with SpO 2 >90% overnight 46 49 50. Patients with more severe COPD and worse daytime ABGs spent a significantly greater proportion of the night with hypoxaemia 51.…”
Section: Long-term Oxygen Therapymentioning
confidence: 99%
“…Nisbet et al. 21 reported that, in the majority of COPD patients, supplemental oxygen delivered at the same rate as that used during the daytime, adequately corrected nocturnal SpO 2 with only 15.8% experiencing an overnight SpO 2 < 90%. Our current results are similar to those of Nisbet et al.…”
Section: Discussionmentioning
confidence: 99%
“…This latter recommendation is implemented with great regional variability around the world, 109 and has been the subject of various studies examining the need to increase supplemental oxygen during the night. 110,111 At least one study has shown a slightly higher degree of hypercapnia with increasing oxygen supplementation per the NOTT guidelines, although the clinical importance is not known. 112,113 Based on the physiological consequences of NOD, and the results of NOTT and MRC trials, it seems intuitive that the treatment for NOD alone (without daytime hypoxemia) should also be supplemental oxygen, and that there should be some measureable impact on health.…”
Section: Treatment Oxygenmentioning
confidence: 99%